2016
DOI: 10.5114/pdia.2015.48044
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum concentrations of the selected cytokines in patients with localized scleroderma

Abstract: A b s t r a c t Introduction: Localized scleroderma is an autoimmune disease primarily affecting the skin. The cause of disease remains unexplained although environmental factors are implicated, which are likely to be responsible for activation of the endothelium and subsequent inflammation leading to excessive synthesis of collagen and extracellular matrix components. Aim: To determine concentrations of interleukin (IL)-27, transforming growth factor (TGF)-β1, TGF-β2, IL-6, and sIL-6R in patients with localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…1 Although LSc and SSc have a number of different disease presentations, both share the common clinical hallmark of skin fibrosis characterized by excessive transforming growth factor-β (TGF-β) activity and extracellular matrix (ECM) production. 2,3 However, underlying mechanisms of this phenomenon are still unclear. 4 Several pro-fibrotic cytokines have been implicated in fibrotic process of scleroderma, including TGF-β, connective tissue growth factor (CTGF), plasminogen activator inhibitor-1 (PAI-1), fibronectin 1 (FN-1), and others.…”
mentioning
confidence: 99%
“…1 Although LSc and SSc have a number of different disease presentations, both share the common clinical hallmark of skin fibrosis characterized by excessive transforming growth factor-β (TGF-β) activity and extracellular matrix (ECM) production. 2,3 However, underlying mechanisms of this phenomenon are still unclear. 4 Several pro-fibrotic cytokines have been implicated in fibrotic process of scleroderma, including TGF-β, connective tissue growth factor (CTGF), plasminogen activator inhibitor-1 (PAI-1), fibronectin 1 (FN-1), and others.…”
mentioning
confidence: 99%
“…The underlying pathogenesis of JLS remains unknown, but upregulation of transforming growth factor-β (TGF-β) production is thought to play a prominent role in excessive collagen deposition [ 8 ]. Previous studies gave variable results as to the serum levels of TGF-β in patients with LS [ 9 ], but highly elevated serum levels were reported in children with linear and generalized types of LS [ 10 ]. Furthermore, a recent report demonstrated that ectopic TGF-β induced vascular endothelial growth factor (VEGF) synthesis in normal fibroblasts, and that overexpression of VEGF was seen in activated systemic sclerosis fibroblasts which acquired autocrine TGF-β signaling following chronic inflammation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Less often the process affects deeper tissues (fascia, muscles and bones), leading to deep atrophy and deformations. The excessive synthesis of collagen type I and III and extracellular components is regarded to play the key role in the formation of characteristic skin lesions [2].…”
Section: Introductionmentioning
confidence: 99%
“…The genetic and environmental factors, as well as microchimerism, are considered to activate keratinocytes to release inflammatory mediators (interleukin-4 (IL-4), IL-6, IL-10, IL-17A, IL-27, interferon-c), which subsequently stimulate lymphocytes, endothelial cells and fibroblasts. Of particular significance, the activation of endothelial cells and lymphocytes provokes fibroblasts to increase collagen synthesis, which clinically manifests as focal skin hardening and active inflammatory border (lilac ring) [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%